2012
DOI: 10.1590/s0102-311x2012001300011
|View full text |Cite
|
Sign up to set email alerts
|

Condição socioeconômica, frequência de escovação dentária e comportamentos em saúde em adolescentes brasileiros: uma análise a partir da Pesquisa Nacional de Saúde do Escolar (PeNSE)

Abstract: This study investigated the association between oral and general health-related behaviors and socioeconomic status, and the relationship between health-related behaviors and toothbrushing among adolescents. The database used here was the National School-Based Health Survey (PeNSE), a cross-sectional population-based study in 2009 with students from 27 Brazilian State capitals. Socio-demographic and health-related behavior data were collected. The survey included 49,189 adolescents (47.5% males), the majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
(34 reference statements)
3
25
0
14
Order By: Relevance
“…In contrast to this unprecedented broad indicator, oral self-care was found in the literature only in a segmented manner. Studies have shown that the higher frequency of tooth brushing was more commonly related to the female sex, 7,12,19,16 better economic conditions, 10,19 better educational level, 16 absence of drinking alcohol 10,16 and smoking, 10,16 practicing physical activities regularly, 8,10 and the type of health service used, whether public or private. 7 One of the variables with greater explanatory capacity of oral self-care characterization was the use of dental floss.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to this unprecedented broad indicator, oral self-care was found in the literature only in a segmented manner. Studies have shown that the higher frequency of tooth brushing was more commonly related to the female sex, 7,12,19,16 better economic conditions, 10,19 better educational level, 16 absence of drinking alcohol 10,16 and smoking, 10,16 practicing physical activities regularly, 8,10 and the type of health service used, whether public or private. 7 One of the variables with greater explanatory capacity of oral self-care characterization was the use of dental floss.…”
Section: Discussionmentioning
confidence: 99%
“…In this stage in which the variable was created, each variable was dichotomized and evaluated as appropriate oral self-care (score 1), according to the conditions considered acceptable by the literature, namely: dental appointment made at least once a year, 12,16 tooth brushing twice a day or more, 18 use of toothbrush, toothpaste and floss, and replacement of toothbrush within less than 6 months; 22 or inadequate self-care (score 0), considered as consisting of the worst conditions.…”
Section: Processing Of Data Variable Outcomementioning
confidence: 99%
See 3 more Smart Citations